MATERIAL FLOW ANALYSIS OF USED BEVERAGES CARTON (UBC) AND FACTORS AFFECTING RECYCLERS TO COLLECT THE UBC MATERIAL (CASE STUDY: BEKASI CITY, WEST JAVA) - Rosida Anggraini, Ella
Aseptic beverage carton packaging or Used Beverages Carton (UBC) consists of polyethylene plastic (15%), paper (80%), and aluminum (5%) which tends to be more difficult to recycle due to composite form, so it tends not to be collected by the informal sector and ends up in landfills. From another perspective, UBC recycling in Indonesia has the potential to become a substitute for imported long fibers to improve the quality of paper, chemical additives, coagulants, and composite products. The problem faced in the UBC recycling industry is the availability of raw materials in the supply chain to sustain the recycling process. The scope of the study was carried out in Bekasi City as a pilot project for the application of UBC material collection from sources initiated by Tetrapak Indonesia in 2020. The research objective is to conduct UBC’s Material Flow Analysis (MFA) with STAN software. In addition, the identification of the factors that influence the intention of recyclers to participate in collecting the UBC was carried out using the Extended Theory of Planned Behavior (ETPB) and processed statistically using SPSS. The results of the MFA model show that efforts to reduce UBC materials to landfill in Bekasi City have been carried out by waste banks and the private waste sector. The projection of reducing UBC waste in 2022 is 1% and the UBC recycled is 0.7% of the total domestic sector UBC waste generation in Bekasi City. Attitude factors, subjective norms, perceived behavioral control, and economically driven simultaneously influence recycling actors' intention to increase UBC recycling efforts by 37.8%. Meanwhile, 62.2% was explained by other factors that were not included in the study. The partial correlation value of the attitude factor is 0.230, the subjective norm is 0.110, perceived behavioral control is 0.073, and the economic driven dominates by 0.368.